Heir to the empire - Zahn, Timothy (New York : Bantam Books, 1991)
The last of the Emperor's warlords has made two vital discoveries that could destroy the fragile new Republic.
New York Times.
School Library Journal.
Adult.
Adult
Keywords: Leia, Princess (Fictitious character) -- Fiction; Skywalker, Luke (Fictitious character) -- Fiction; Solo, Han (Fictitious character) -- Fiction; Leia, Princess (Fictional character) -- Fiction; Science fiction; Skywalker, Luke (Fictional character) -- Fiction; Solo, Han (Fictional character) -- Fiction; Science fiction